Rogue Waves : Climate Change and Firm Performance - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2022)
Climate change is an existential threat to the global economy and financial markets. There is a large body of literature documenting potential macroeconomic consequences of climate change, but firm-level empirical research on how climate change affects the performance of firms remains scarce. This paper aims to close this gap by empirically investigating the impact of climate change vulnerability on corporate performance using a large panel dataset of more than 3.3 million nonfinancial firms from 24 developing countries over the period 1997-2019. We find that nonfinancial firms operating in countries with greater vulnerability to climate change tend to experience difficulty in access to debt financing even at higher interest rates, while being less productive and profitable relative to firms in countries with lower vulnerability to climate change. We confirm these findings with alternative measures of climate change vulnerability. Furthermore, partitioning the sample reveals that these effects are significantly greater for smaller firms, especially in high-risk sectors and countries and countries with weaker capacity to adapt to and mitigate the consequences of climate change.